A PROSPECTIVE RANDOMIZED STUDY ON RAISE OF LIVER ENZYMES OFSODIUM VALPROATE AND LEVETIRACETAM IN CHILDHOOD GENERALIZEDEPILEPSY IN A TERTIARY CARE HOSPITAL. - Dr.Ramadevi Devagudi; Dr. Gosala Sree Lakshmi; Dr. Divya Gayatri Penupothu; Dr. Padmavathi Devagudi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Sodium valproate and levetiracetam are widely prescribed for childhood generalized epilepsy. Sodium valproate is known to cause hepatic enzyme elevation, whereas levetiracetam’s effect on liver function is less documented. Monitoring liver enzymes is essential to ensure drug safety in pediatric patients. Methods: This prospective, randomized study was conducted in the Department of Pediatrics, [GGH,Kadapa], over 3 months. A total of 100 children aged 2–14 years with newly diagnosed generalized epilepsy were randomly assigned to receive sodium valproate (n=50) or levetiracetam (n=50). Baseline liver function tests (LFTs) were performed before therapy initiation and repeated at 1 and 3 months. Primary outcome measures included changes in serum alanine transaminase (ALT), aspartate transaminase (AST), and alkaline phosphatase (ALP) levels. Clinically significant elevation was defined as >2× the upper limit of normal. Results: By the 3-month follow-up, mean ALT and AST levels in the sodium valproate group had increased significantly from baseline (p< 0.05), with clinically significant elevation in 14% of patients. The levetiracetam group showed minimal, non-significant changes, with only 2% exhibiting mild elevations. No patient developed acute liver failure or required discontinuation due to hepatotoxicity. Conclusion: Sodium valproate is associated with a higher frequency of liver enzyme elevation compared to levetiracetam in children with generalized epilepsy. Regular LFT monitoring is strongly recommended for patients on sodium valproate, whereas levetiracetam may offer a safer hepatic profile in this age group.